2022
DOI: 10.1108/ilt-12-2021-0472
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental research on the influence of lubrication on the comprehensive friction of TGDI engine

Abstract: Purpose This paper aims to investigate the effects of low-viscosity and ultralow-viscosity engine oils on the comprehensive friction and fuel economy of turbocharged gasoline direct injection (TGDI) through simulation analysis and experiments. Design/methodology/approach Numerical analysis models of friction loss for reciprocating, crankshaft and valve train are established. Based on the FAST, the friction loss of 24 specific parts of a TGDI engine was analyzed. Finally, the engine test bench was built, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It allowed users to design the craft form or pattern they want in real-time with the synergy of virtual reality technology and augmented reality technology, which greatly increases the practicality and convenience of this model. Virtual reality technology includes various technologies such as computer graphics, simulation, computer networks, interactive design, artificial intelligence, multimedia, and sensing technology [27][28][29][30]. The user interacts naturally with the computer through a combination of user interface and sensors, thus enabling the user to gain a sense of immersion and fully integrate into the created virtual world, as shown in Figure 2.…”
Section: Figure 1 Arts and Crafts Virtual Design Modelmentioning
confidence: 99%
“…It allowed users to design the craft form or pattern they want in real-time with the synergy of virtual reality technology and augmented reality technology, which greatly increases the practicality and convenience of this model. Virtual reality technology includes various technologies such as computer graphics, simulation, computer networks, interactive design, artificial intelligence, multimedia, and sensing technology [27][28][29][30]. The user interacts naturally with the computer through a combination of user interface and sensors, thus enabling the user to gain a sense of immersion and fully integrate into the created virtual world, as shown in Figure 2.…”
Section: Figure 1 Arts and Crafts Virtual Design Modelmentioning
confidence: 99%
“…It was found that the weight of the hollow shaft was reduced by 29.7% at variable speeds of 5000-10000 r/min. The literature [27] simulated and analyzed the effect of low-viscosity and ultra-low-viscosity engine oils on the integrated friction of turbocharged gasoline direct injection and developed a numerical analysis model of the friction loss of reciprocating crankshafts for testing the external and general characteristics during engine speed change. An adaptive control method based on an adaptive neural network inverse system and a two-degree-of-freedom internal model controller was proposed in the literature [28].…”
Section: Introductionmentioning
confidence: 99%